Selection of a suitable plant for phytoremediation in mining artisanal zones - Toledo Vargas, J. (2016)
A study was undertaken with the aim of identifying a suitable plant for the phytoremediation of metal-polluted soil from an artisanal mining area in Ecuador. Three zones including a natural zone (NZ), abandoned zone (AZ) and intensive zone (IZ) were selected. Three common native plants grown in the three zones were identified and collected, including Miconia zamorensis, Axonopus compressus and Erato polymnoides. The percentage of arbuscular mycorrhizal colonisation was also analysed in the root samples of these candidate hyperaccumulator species. Analysis of the soils and plants collected from the different zones showed that the concentrations of Pb, Zn, Cu and Cd were comparatively less in the NZ, higher in the AZ and IZ, and highest in the AZ for all the metals. The concentration of all these metals in plant tissues was the highest in E. polymnoides. The data analysis including the metal accumulation index (MAI),bioconcentration factor (BCF) and translocation factor (TF) strongly identified E. polymnoides as a hyperaccumulateo plant.